COVID-19 pandemic anxiety, academic stress, and quality of life among college students in the Philippines: A mediation study - Cleofas, Jerome V.; Rocha, Ian Christopher N.; Parcon, Rey G. (Jurnal Cakrawala Pendidikan, 2023)
Cognizant of the specific pathways that students' lives can be impacted by the Coronavirus Disease 2019 (COVID-19) pandemic, this study investigated the relationship between COVID-19 pandemic anxiety and quality of life of Filipino college students and examined the mediating role of academic stress in this relationship. A total of 1,024 students enrolled in Philippine universities and colleges participated in this cross-sectional analytical study. Findings suggest that pandemic anxiety was positively correlated with quality of life (c=.399, p=0.002). When academic stress was added as a mediator, pandemic anxiety was found to have a negative indirect effect on quality of life (ab=-.410, p<.001), and maintained a positive direct effect on quality of life (c'=.809, p<.001), yielding an inconsistent mediation model among the three variables. This means that COVID-19 pandemic anxiety has a double-edged effect on quality of life, with its negative effect explained through the pathway of academic stress. It is recommended that stakeholders in college education employ interventions to address academic stress among students.